Formal Versus Informal Finance : Evidence from China - Ayyagari, Meghana; Demirgüç-Kunt, Asli (World Bank, Washington, DC, 2012)
China is often mentioned as a counterexample to the findings in the finance and growth literature since, despite the weaknesses in its banking system, it is one of the fastest growing economies in the world. The fast growth of Chinese private sector firms is taken as evidence that it is alternative financing and governance mechanisms that support China's growth. This paper takes a closer look at firm financing patterns and growth using a database of 2,400 Chinese firms. The authors find that a relatively small percentage of firms in the sample utilize formal bank finance with a much greater reliance on informal sources. However, the results suggest that despite its weaknesses, financing from the formal financial system is associated with faster firm growth, whereas fund raising from alternative channels is not. Using a selection model, the authors find no evidence that these results arise because of the selection of firms that have access to the formal financial system. Although firms report bank corruption, there is no evidence that it significantly affects the allocation of credit or the performance of firms that receive the credit. The findings suggest that the role of reputation and relationship based financing and governance mechanisms in financing the fastest growing firms in China is likely to be overestimated.